Factors impacting customer satisfaction in the hotel restaurant at Kota Kinabalu, Sabah: a study of hotel restaurant attributes - Marry Tracy Pawan (Penerbit Universiti Malaysia Sabah, 2019)
The purpose of this research was to access the influence of hotel restaurant attributes towards customer satisfaction in the hotel restaurant. In this paper, three of the hotel restaurant attributes will be discussed. The main objectives of this study are to examine the relationship between food quality, service quality and atmosphere towards customer satisfaction in the hotel restaurant. This study using a quantitative approach and questionnaire has been distributed to the respondents who have dined in at the hotel restaurant in the Kota Kinabalu area. Meanwhile, the data for this study will be analyzed using Partial Least Square via Structural Equation Modelling. The result shows that food quality, service quality and atmosphere have a significant effect on customer satisfaction. This study will assist the hotel industry in Kota Kinabalu as generally in obtaining a better picture of the key factor that determines customer satisfaction to stay competitive with another freestanding restaurant.